Sistem Temu Kembali Informasi Pada Gejala Autisme Dengan Metode Vector Space Model - Bayu Sugara; Dody Dody; Donny Donny (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Information is now very easy to get anywhere. Information technology, especially the internet, strongly supports the exchange of information very quickly. The internet has become an information and communication media that has been used by many people with many interests, especially in taking large-scale information data, Unfortunately the information presented is sometimes less relevant. Quality information is influenced by relevance, accuracy and on time. However, there are not many effective search systems available. This study discusses the implementation of an information retrieval system to find and find symptoms of autism disorders using the Vector Space Model (VSM) method. Vector Space Model (VSM) is a model used to measure the similarity between a document and a query. In this model, queries and documents are considered vectors in n dimensional space. Where n is the number of all terms listed. The purpose of this study was to design an information retrieval software to find and match the symptoms of autism disorders. By using Vector Space Model, it is hoped that it can provide a solution to the search engine to provide text matching information in the database using certain keywords, the results of the matching are presented in the form of ranks.